Assembly–disassembly switching of self-sorted nanotubules forming dynamic 2-D porous heterostructure. Issue 25 (1st March 2018) - Liu, Xin; Li, Huichang; Kim, Yongju; Lee, Myongsoo
Abstract : Self-sorted tubules and sheets are reversibly merged into 2-D porous heterostructure in response to a pH change. Abstract : We report the pH-driven formation of a dynamic 2-D porous heterostructure through assembly–disassembly switching of the stacked macrocycles of nanotubules and their subsequent spreading on the surfaces of a self-sorted sheet assembly in a hierarchical co-assembly. The 2-D ordered porous heterostructure is able to discriminate spherical C60 from flat coronene through shape selective adsorption.